2021
DOI: 10.14740/wjon1367
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Lung Cancer Community

Abstract: Since the outbreak of 2019 novel coronavirus disease (COVID-19) induced by a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the pandemic has become a global catastrophe. Patients with cancer especially lung cancer are more vulnerable and susceptible to get infected by the virus SARS-CoV-2. The overwhelming impact of COVID-19 on lung cancer community may result in rise of the incidence and mortality of lung cancer. It would become more obvious in future retrospective studies. Lung cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…But in addition to the impact on hospitalizations and mortality, the question arises with a decline in new cancer diagnoses. Due to the overlap of SARS-CoV-2 symptoms with those of lung cancer [ 44 ], new lung cancer diagnoses were accounted for in many of our patients. A Canadian study [ 45 ] showed that in 2020 there were 103 cases, compared to 130 diagnosed in 2019 (−34.7%), which is higher than the number registered in our study (6.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But in addition to the impact on hospitalizations and mortality, the question arises with a decline in new cancer diagnoses. Due to the overlap of SARS-CoV-2 symptoms with those of lung cancer [ 44 ], new lung cancer diagnoses were accounted for in many of our patients. A Canadian study [ 45 ] showed that in 2020 there were 103 cases, compared to 130 diagnosed in 2019 (−34.7%), which is higher than the number registered in our study (6.5%).…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients’ access to the hospital was limited if strictly necessary [ 44 ]. On the other hand, guaranteeing cancer treatments was a priority since delays in treatment could cause an increase in morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…First, the compromised immune system associated with the higher expression of ACE2 in lung cancer tissue could promote viral infection and predispose to severe pathology. Second, a further increase of specific chemokine as C-X-C motif or CÀC motif and interleukin (IL)-1 due to SARS-CoV-2 infection in lung cancer patients already characterized by a high level of inflammation could lead to the cytokine storm that is associated with the worst outcome and a loss of function of the lung [28]. Third, in patients with lung cancer, SARS-CoV-2 infection could quickly progress to a severe phase because in these patients the immune system is weakened by the chemotherapy, radiotherapy, or immune checkpoint inhibitors treatment.…”
Section: Mechanisms Of Sars-cov-2 Infection: Implications For Severe ...mentioning
confidence: 99%
“…Several studies have revealed that patients with malignancy are of the vulnerable population to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and have a higher mortality rate than patients without cancer among in-patients with COVID-19 [3][4][5][6]. Some of these patients have delayed diagnosis and treatment of the disease due to the fear of the COVID-19 pandemic, which in turn affects the survival rate of patients [7].…”
Section: Introductionmentioning
confidence: 99%